The effectiveness and feasibility of online prolonged exposure therapy for post-traumatic stress among university students - Slabbert, Maryna (Rhodes University, Faculty of Humanities, Department of Psychology)
Research has found that 70.6% of university students reported exposure to several traumatic events (Hoffman, 2002). Considering the high prevalence of trauma exposure among South African university students, many are at risk of developing post-traumatic stress disorder (PTSD) (Iribarren, Prolo, Naegos & Chiappelli, 2005). Prolonged Exposure Therapy (PE) is regarded as a first-line trauma therapy for PTSD (Foa, Hembree, Rothbaum, & Rauch, 2019). During the Covid-19 pandemic, public health guidelines for physical distancing reduced access to face-to-face mental health care. In response to this, many health care providers adapted to pandemic constraints by meeting their clients online, through Zoom, for example (Wells et al., 2020). Considering the prevalence of trauma exposure among university students, as well as the increased necessity of teletherapy, the study aimed to investigate the effectiveness and feasibility of online PE for PTSD among university students in a South African setting. The study employed Single-Case Experimental Design (SCED) as basis for its research design. Participants included a sample of Rhodes University students (n = 3) who were recruited through purposive sampling. Prior to the intervention, all three participants met the criteria for PTSD, and comorbid depression. Based on the measures used, two of the three participants did not meet the criteria for PTSD post-intervention. In terms of depression symptoms, one participant did not meet the criteria for depression post-intervention, and another participant showed a decrease in depression symptoms. Regarding the feasibility of online PE, all three participants reported the intervention to be feasible, acceptable, and appropriate. Overall, the study provides preliminary results to support the effectiveness and feasibility of online PE. It also gives insight into the value of intervention research and how it can ameliorate PTSD in a South African setting, as well as other low- and middle-income countries (LMICs).
Keywords: Exposure therapy; Post-traumatic stress disorder; College students -- South Africa; Prolonged exposure therapy; Online therapy